Process of sanitation of certified free properties of brucellosis and tuberculosis in the State of São Paulo - Carraro, Paulo Eduardo; Bürger, Karina Paes (UFBA - Universidade Federal da Bahia, 2019)
SUMMARY The aim of this study was to analyze the sanitation process of the properties certified as free of brucellosis and tuberculosis in the State of São Paulo. However, 14 properties with free certification, between the years 2001 and 2016, were identified and analyzed. The municipalities of the properties were geoprocessed on the map of the state livestock circuit. Through descriptive statistics, a semi-structured questionnaire was evaluated with questions related to the profile of properties (characteristics of the owner, property, production and questions related to human, animal and environmental health) and to the sanitation process. The results showed that, in the state of São Paulo, the 14 certified properties free of brucellosis and tuberculosis were not uniformly distributed, it had herds with 90 to 500 animals, monthly veterinary assistance and milk production was technified with medium or large production capacity milk daily. The owners had an average age of 63, 92.8% (13/14) of them with a higher education level and found difficulties to obtain and maintain the certificate. These properties, even in the process of sanitation, had reinfection in the herd, evidencing the complexity in combating the diseases and the need for more joint actions among the whole community.

RESUMO O objetivo deste trabalho foi analisar o processo de saneamento das propriedades certificadas como livres de brucelose e tuberculose do Estado de São Paulo. Para tanto, 14 propriedades com certificação livre, entre os anos de 2001 e 2016, foram identificadas e analisadas. Os municípios das propriedades foram geoprocessados no mapa dos circuitos pecuários do Estado. Por meio da estatística descritiva, avaliou-se um questionário semiestruturado com questões relativas ao perfil das propriedades (características do proprietário, da propriedade, da produção e perguntas relacionadas à saúde humana, animal e ambiental) e ao processo de saneamento. Os resultados evidenciaram que no Estado de São Paulo as 14 propriedades certificadas livres de brucelose e tuberculose não se distribuíram uniformemente, possuíam rebanhos com 90 a 500 animais, tendo assistência veterinária mensal, e a produção leiteira era tecnificada, com capacidade média ou grande de produção diária de leite. Os proprietários tinham em média 63 anos de idade, 92,8% (13/14) deles com nível superior de escolaridade e encontraram dificuldades para obter e manter o certificado. Essas propriedades mesmo estando em processo de saneamento tiveram reinfecção no rebanho, evidenciando a complexidade em combater as enfermidades e a necessidade de mais ações conjuntas entre toda a comunidade.
Processo de saneamento das propriedades certificadas como livres de brucelose e tuberculose no Estado de São Paulo
Keywords: control; eradication; health program; milk; zoonosis; controle; erradicação; leite; programa sanitário; zoonoses